Rental Regulation and its Consequences on Measures of Well-Being in the Arab Republic of Egypt - Lara Ibarra, Gabriel; Mendiratta, Vibhuti; Vishwanath, Tara (World Bank, Washington, DC, 2017)
The paper delves into the implications of a failure to account for rental regulation in the measurement of households' welfare, poverty, and inequality when using household surveys. Exploiting previously unavailable data for the Egyptian case, the paper illustrates the long-lasting distortions in the rental market that the 1977 rental law has created. The paper finds evidence that earlier studies may have substantially underestimated households’ welfare in urban areas and overestimated urban poverty. National poverty rates show smaller corrections, as poverty is mainly a rural phenomenon in the Arab Republic of Egypt. An appropriate measure of welfare also led to downward corrections in inequality in urban Egypt, while increasing the inequality across regions. These effects counterbalance each other and nationwide inequality estimates are affected only slightly.